A comparative study: The effect of current loading modes on the cold start-up process of PEMFC stack. (1st January 2022) - Lei, Le; He, Pu; He, Peng; Tao, Wen-Quan
Highlights: A transient numerical model of the PEMFC stack cold start-up is presented. The effects of current loading modes on cold start-up are detailly analyzed. The requirements to evaluate the current loading modes in the start-up are proposed. An optimal current loading mode for the cold start-up process is recommended. Abstract: The start-up of the proton exchange membrane fuel cell (PEMFC) at temperatures below the freezing point is considered one of the major obstacles hindering the widespread commercialization applications of fuel cells. In this work, a one-dimensional transient numerical model is adopted to study the effects of five different current loading modes on the stack start-up from −20 °C. They are constant current loading mode, constant slope ramp loading mode, variable slope ramp loading mode, zigzag current loading mode, and stepwise-changed current loading mode. The detailed comparative analyses are presented for a better understanding of the cold start-up process. Three levels (good, appropriate, and inferior) are used to evaluate the performance of the current loading modes. The results show that the stepwise-changed current loading mode is the best among the five modes because it has the advantages of appropriate start-up time, temperature rising rate, ohmic resistance, heat generation rate, ice volume fraction, and water production rate.